(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2022)
This study was aimed to boost up the dissolution rate of a sparingly aqueous soluble BCS Class II drug pitavastatin (PTV) by solid dispersion (SD) techniques using two hydrophilic polymers poloxamer 407 and hydroxypropylmethylcellulose (HPMC). Low aqueous solubility of PTV is associated with less oral bioavailability, and a real challenge in preparing appropriate dosage form. To enhance the aqueous solubility, physical mixing and SD formulations of PTV were developed by fusion and solvent evaporation methods using two hydrophilic polymers, poloxamer 407 and HPMC. Scanning electron microscopy (SEM) investigation indicated that PTV molecules were homogeneously dispersed in carrier prepared by different formulation methods at 1:2 and 1:3 ratios of PTV: polymer assuming amorphous SD state. The thermogravimetric profiles demonstrated that PTV was stable up to 198°C and began to decompose rapidly with significant weight loss as the temperature was raised over 190°C. Formulations prepared by SD techniques were stable at high temperature. In vitro studies illustrated that cumulative drug release of PTV: HPMC/poloxamer 407 formulations prepared by physical mixing, fusion and solvent evaporation techniques were better compared to pure PTV powder (61.42±0.91%). Among all the approaches, formulations prepared by solvent evaporation and fusion methods displayed higher cumulative releases of PTV than physical mixing formulations. The results of current study clearly indicated that PTV: HPMC/poloxamer 407 (1:2) formulations (S3, S1) developed by solvent evaporation method possess enhanced dissolution profile (96.06%; 95.62%) than the fusion SD formulations (F3; 94.62%, F1; 87.05%). Whereas PTV physical mixing formulations (P2; 82.32%, P4; 80.28%) containing high amount of carrier polymers (ratio 1:3) exhibited superior in vitro dissolution rates than formulations (P3; 68.70%, P1; 71.52%) having less quantity (ratio 1:2) of HPMC/poloxamer 407. It is apparent from the findings of this study that SD formulations (S3, S1, F3, F1) of PTV with HPMC/poloxamer 407 is a very promising approach for improving the in vitro dissolution profile of the sparingly aqueous soluble PTV. Moreover, 1:2 ratio formulations prepared by fusion and solvent evaporation SD approaches were found more effective to upgrade the release rate of PTV than the 1:3 formulations. Dhaka Univ. J. Pharm. Sci. 20(3): 325-336, 2022 (June) Centennial Special Issue